Pelvic radiation in stage I endometrial adenocarcinoma with high-risk attributes - Marchetti, D L; Caglar, H; Driscoll, D L; Hreshchyshyn, M M (Gynecologic oncology, 1990)
From 1977 to 1987, 45 patients with FIGO stage I endometrial adenocarcinoma with high-risk attributes and disease confined to the pelvis were prospectively treated with postoperative pelvic radiation. By study design, all patients underwent staging laparotomy with pelvic and paraaortic lymphadenectomy. All patients had either grade 1 or 2 adenocarcinoma and greater than 50% myometrial invasion or grade 3 adenocarcinoma with less than or greater than 50% myometrial invasion. The estimated 5-year survival for all 45 patients was 77% and the 5-year disease-free interval was 82%. Regional control was achieved in 89% of all patients, with 4% recurring at distant sites. When patients were stratified according to surgical-pathologic findings, 33 patients with disease confined to the uterus or uterus and pelvic nodes (surgical stage I) had estimated 5-year survival and disease-free interval of 88%. Of these 33 patients, 10 with grade 1 or 2 adenocarcinoma and deep myometrial invasion had 5-year disease-free intervals of 100%, while 23 patients with grade 3 adenocarcinoma with less than or greater than 50% myometrial invasion had disease-free intervals of 79 and 91%, respectively. From these results, it was concluded that patients with high-risk attributes demonstrated to have disease confined to the uterus or uterus and pelvic nodes can achieve excellent survival following surgical staging and postoperative pelvic radiation.